Human Energy Expenditure and Postural Coordination on the Mechanical Horse. Issue 4 (4th July 2017) - Baillet, Héloïse; Thouvarecq, Régis; Vérin, Eric; Tourny, Claire; Benguigui, Nicolas; Komar, John; Leroy, David
ABSTRACT: The authors investigated and compared the energy expenditure and postural coordination of two groups of healthy subjects on a mechanical horse at 4 increasing oscillation frequencies. Energy expenditure was assessed from the oxygen consumption, respiratory quotient, and heart rate values, and postural coordination was characterized by relative phase computations between subjects (elbow, head, trunk) and horse. The results showed that the postural coordination of the riders was better adapted (i.e., maintenance of in-phase and antiphase) than that of the nonriders, but the energy expenditure remains the same. Likewise, we observed an energy system shifting only for nonriders (from aerobic to lactic anaerobic mode). Finally, cross-correlations showed a link between energy expenditure and postural coordination in the riders (i.e., effectiveness).